Family Values and the Star Phenomenon: Strategies of Mutual Fund Families - Nanda, V. (Review of Financial Studies, 2003)
We examine the extent to which a fund's cash flows are affected by the stellar performance of other funds in its family – and consequences of such spillovers. We show that star performance results in greater cash inflow to the fund and to other funds in its family. Moreover, families with higher variation in investment strategies across funds are shown to be more likely to generate star performance. We argue that spillovers may induce lower ability families to pursue star-creating strategies. Consistent with our conjecture, families with high variation in investment strategies across funds significantly underperform low-variation families. Copyright 2004, Oxford University Press.